Tuhan dalam Mistik Islam Kejawen (Kajian atas Pemikiran Raden Ngabehi Ranggawarsita) - Kholid Karomi (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2013)
Javanese people were known as religious communities, but there are some syncretic people among them who likely to compromise the things are somewhat different even contrary to religion. They also do not question the right or wrong in religion, pure or not, so they see all religions are true. Raden Ngabehi Ranggawarsita was a figure representing this. He was born and raised in between two major traditions, Islamic tradition and Javanese tradition. He received Islamic tradition from pesantren and Javanese tradition from his environment, Surakarta Palace. These two traditions affected his thinking, not exception his thought about God. Because it also, the concept of God which was initiated by Ranggawarsita did not fully represent the fundamental values of Islam (tawhid). He had has the Manunggaling Kawula Gusti in view on God. This concept showed that Ranggawarsita as adherent of kejawen and in a time he was a Muslim. This paper will look critically at the Ranggawarsita’s view on God.